P092/O15 Synovial derived Th17-lymphocytes from patients with juvenile idiopathic arthritis induce cartilage degradation by synovial fibroblasts mediated by MMP9 in an experimental animal model. (March 2019) - Giani, T; Margheri, F; Del Rosso, M; Maggi, L; Annunziato, F; Cimaz, R
Abstract : Career situation of first and presenting author: Student for a master or a PhD. Introduction: The synovial fluid of Juvenile idiopathic Arthritis (JIA) is rich of Th17 and of Th-17-derived CD4+ CD161+ cells, also called non-classic-Th1. How such subpopulations drive the JIA joint damage is still a subject of great interest especially in light of the possible use of biological drugs able to selectively inhibit the activity of specific cytokines. Objectives: To clarify the role of Th17 and non-classical Th1 lymphocytes in the pathogenesis of joint cartilage destruction by synovial fibroblasts (SFbs). Methods: The role of different subsets of CD4+T cells was observed in the activation of SFbs in terms of cartilage degradation by normal and JIA SFbs and induction of proteases both in vitro and in vivo, using a SCID Mouse model through the 'inverse wrap' implantation technique. Results: JIA SFbs produce large amounts of MMP9 and efficiently degrade fragments of human cartilage wrapped in a collagen matrix containing the fibroblasts themselves and grafted under-skin on SCID mice (the 'inverse wrap model'). Similar effects were observed with SFbs of healthy subjects incubated with conditioned media of Th17 and of non-classic Th1. We shown that Th17 induce MMP9 in SFbs, while non-classic Th1 act mainly by inducing urokinase-plasminogen-activator over-activity. Conclusions: IL-17 triggers the pathogenic chain leading to joint damage in patients with JIA. References: Maggi L, et al . T cell subpopulations in juvenile idiopathis arthritis and their modifications after biotherapies. Autoimmun Rev 2016;15:1141–44. Nistala K, et al . Th17 plasticity in human autoimmune arthritis is driven by the inflammatory environment. Proc Natl Acad Sci U S A 2010;107:14751–6. Miossec P, Korn T, Kuchroo VK. Interleukin-17 and type 17 helper T cells. N Engl J Med. 2009 August 27;361:888–98. Maggi L, et al . Judex M, et al . 'Inverse wrap': an improved implantation technique for virus transduced synovial fibroblasts in the SCID mouse model forrheumatoid arthritis. Mod Rheumatol 2001;11:145–50. Del Rosso M, et al . Multiple pathways of cell invasion are regulated by multiple families of serine proteases. Clin Exp Metastasis 2002;19:193–207. Beringer A, Noack M, Miossec P. L-17 in Chronic Inflammation: From Discovery to Targeting. Trends Mol Med 2016 March;22:230–241. Miossec P. Update on interleukin-17: a role in the pathogenesis of inflammatory arthritis and implication for clinical practice. RMD Open 2017 February 15;3. Disclosure of Interest: None declared.